Fiscal Decentralization and Municipal Performance in Nepal - Khanal, Gopi (Journal of Management and Development Studies, 2016)
The literature on decentralization is inconsistent to explain the effectiveness of fiscal decentralization on local governance. Based on the descriptive data on revenue and expenditure decentralization from 51 Nepali municipalities, this study found empirically significant positive relationship between revenue decentralization and municipal performance. However, regression results showed an insignificant association between fiscal transfer and municipal overall performance. The study suggests that devolving power to tax is associated with better municipal performance than downloading expenditure responsibilities to municipalities through fiscal transfers.